2014
DOI: 10.1063/1.4898698
|View full text |Cite
|
Sign up to set email alerts
|

Understanding pop-ins in spherical nanoindentation

Abstract: Pop-ins, or sudden displacement-bursts at constant load in a nanoindentation test, are typically attributed to the difficulty of setting up potent dislocation sources in the very small indentation zones in these experiments. Such displacement (and strain) bursts would intuitively indicate a sharp drop in stress during the pop-in event itself. However, spherical indentation stress-strain curves routinely exhibit a high and stable indentation stress value during the pop-in, and the indentation stresses decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…In those studies, pop-ins disappeared after the introduction of small amounts of plastic deformation [136]. Therefore, in the prior studies, it was concluded that the pop-ins were a consequence of the difficulty of activating dislocation sources within the primary indentation deformation zone [54,[120][121][122]124,125]. In the present work, the lack of pop-ins in the 810-10-000 sample is consistent with the previous observations described above.…”
Section: Nanoindentation and Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In those studies, pop-ins disappeared after the introduction of small amounts of plastic deformation [136]. Therefore, in the prior studies, it was concluded that the pop-ins were a consequence of the difficulty of activating dislocation sources within the primary indentation deformation zone [54,[120][121][122]124,125]. In the present work, the lack of pop-ins in the 810-10-000 sample is consistent with the previous observations described above.…”
Section: Nanoindentation and Resultssupporting
confidence: 90%
“…A pop-in is identified as a sudden jump in the indentation displacement at a roughly constant load (the tests are performed in load control) and appears as a strain burst in the indentation stress-strain curves (see the measurement for the ferrite region in Figure 7). Pop-in events have been observed extensively in previous work [54,[120][121][122][123][124][125] and were attributed to the difficulty of activating dislocation sources in the very small primary indentation zone. These pop-ins make it difficult to accurately estimate the indentation yield strength.…”
Section: Nanoindentation and Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…3). This phenomena is commonly referred to as 'staircase yielding' [20,28,29] for loadcontrolled indentations, where the indentation strain (or depth) excursions correspond to discrete plastic deformation events and are separated by loading portions that are predominantly elastic [14,15,30]. (ii) At intermediate indenter sizes (5 μm and 10 μm radii indenters) the series of pop-ins continues up to a critical strain level, and is then followed by rapid work hardening in the indentation stress-strain response.…”
mentioning
confidence: 99%
“…It should be noted that pop-ins occur quite regularly in indentation tests on annealed samples, even when the indentations are performed in regions far from the grain boundaries, especially in the tests with the small indenter tips. 59,60 However, such pop-ins are referred as incipient pop-ins and are generally attributed to the difficulty of instantiating a dislocation source in the very small indentation zone involved in such tests. Interestingly, the incipient pop-ins have been observed to be suppressed or mitigated in indentations conducted close to the grain boundary (compared to those conducted in the grain interior).…”
Section: Grain/phase Boundaries In Metalsmentioning
confidence: 99%